2023
DOI: 10.1097/moo.0000000000000898
|View full text |Cite
|
Sign up to set email alerts
|

Selective neurectomy for nonflaccid facial palsy

Abstract: Purpose of review To review the evolving role of selective neurectomy in the management of patients with synkinesis including the history of selective neurectomy, operative techniques, and clinical outcomes. Recent findings Modified selective neurectomy alone or in conjunction with other procedures achieves more durable outcomes based on objective measures such as time to recurrence of symptoms and units of botulinum toxin required postoperatively. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…50 Studies have demonstrated significant improvements in patient-reported smile outcomes, facial tightness, and discomfort and a reduced need for botulinum toxin use. [50][51][52] However, oral incompetence and articulation difficulties are recognized complications of this procedure. 51,52 Electrical stimulation can be used to promote the stimulation of muscles during the denervation period, thereby promoting functional recovery.…”
Section: Botulinum Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Studies have demonstrated significant improvements in patient-reported smile outcomes, facial tightness, and discomfort and a reduced need for botulinum toxin use. [50][51][52] However, oral incompetence and articulation difficulties are recognized complications of this procedure. 51,52 Electrical stimulation can be used to promote the stimulation of muscles during the denervation period, thereby promoting functional recovery.…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…[50][51][52] However, oral incompetence and articulation difficulties are recognized complications of this procedure. 51,52 Electrical stimulation can be used to promote the stimulation of muscles during the denervation period, thereby promoting functional recovery. 53,54 Despite some success in treating patients with acute Bell's palsy, 55 it has been suggested that stimulation could disrupt reinnervation and be counterproductive in improving overall facial nerve function by inducing synkinesis and is not used in our center.…”
Section: Botulinum Toxinmentioning
confidence: 99%